Outcomes of antiretroviral treatment program in Ethiopia: Retention of patients in care is a major challenge and varies across health facilities - Kloos Helmut; Mariam Damen Haile; Tesfaye Dessalegn; Kiflie Abiyou; Assefa Yibeltal; Edwin Wouters; Laga Marie; Van Damme Wim (BMC, 2011)
Abstract Background Many resource-limited countries are scaling up antiretroviral treatment (ART) towards universal access. However, there are few studies which evaluated outcomes of ART programs in these countries. In addition, these studies generally include a limited number of facilities and patients creating a clear need for studies with a wide range of facilities and large numbers of patients. In this study, we intended to evaluate the outcomes of the ART services in 55 health facilities in Ethiopia. Methods A retrospective longitudinal study was conducted to determine levels of patient retention in care, CD4 count and shift to second-line ART regimen in 30 hospitals and 25 health centers selected as sentinel sites for monitoring the outcomes of ART program in the country. The outcomes were determined at baseline, after 6, 12 and 24 months on ART. Data was collected from routine patient registers and charts, and entered and analyzed using EPI-Info statistical software. Results Health facilities were able to retain 29,893 (80%), 20,079 (74%) and 5,069 (68%) of their patients after 6, 12 and 24 months on ART, respectively. Retention rates vary across health facilities, ranging from 51% to 85% after 24 months on ART. Mortality was 5%, 6% and 8% after 6, 12 and 24 months on ART. More than 79% of patients with available CD4-cell counts had a baseline CD4-cell counts less than 200 cells per micro-liter of blood. The median CD4-cell counts (based on patients who were retained after 24 months on ART) increased from 125 (inter-quartile (IQ), 68-189) at baseline to 242 (IQ, 161-343), 269 (IQ, 185-380) and 316 (IQ, 226-445) cells per micro-liter after 6, 12, and 24 months on ART, respectively. The transition to second-line ART remained very low, 0.33%, 0.58% and 2.13% after 6, 12 and 24 months on ART. Conclusion The outcomes of the ART services in the 55 health facilities in Ethiopia are similar to those in other countries. Retention of patients in care is a major challenge and varies across health facilities with high, medium and low retention rates. We therefore recommend further studies to understand the organization of care in health facilities with high, medium and low retention rates. It is also imperative that early initiation of patients on ART is taken seriously as more than 79% of the patients had baseline CD4-cell counts less than 200 cells per micro-liter of blood. Finally, we recommend that the shift to second-line ART might be too low and warrants close monitoring.